Studi Waktu Kerja untuk Meningkatkan Produktivitas Kerja pada Pembuatan Upper Sandal - Abdi, Haris; Herlina, Herlina (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
KUB Capable of Jaya is an industrial business formed from skills training to improve the economy and standard of living of the residents. This company produces goods that focus on types of footwear, namely hotel slippers, sandals, shoes, and upper sandals. In the upper sandal production process, problems were found at work time where workers did not have a time reference and target production in the production process. This causes a lot of free time and affects the speed of workers in doing work which will have an impact on production results that cannot meet the number of customer orders. The purpose of this research is to find out the standard production time, standard production output, and the number of workers needed so that the amount of production can meet the target order. The methods used to solve this problem are the work sampling method, standard output, and workload analysis. The standard time to produce 1 unit of upper sandals is 68,24 seconds, the standard output produced in 1 day is 422 units or 211 pairs, and the number of workers in the cutting process is 5 people, 1 person is punching holes, 1 person is installing buckles, 1 person for the buckle locking process, and 1 person for the installation/finishing process